Chasing impact - how hybrid new ventures shape markets for sustainability - Syväri, Mariia (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2022)
This study contributes to the market-shaping research in the field of business-to-business marketing. Market shaping refers to the purposeful efforts of actors to change market characteristics or to construct new markets. Existing research has focused on incumbent firms or collectives striving to improve their commercial viability through market shaping. However, few studies focus on market shaping undertaken explicitly for the renewal of existing markets towards sustainability. Moreover, we have scant understanding of how market shaping is conducted by hybrid new ventures despite the unprecedented opportunities that digitalization is providing for small actors to exercise their agency. Hybrids refer to entrepreneurial ventures designed from start to equally pursue commercial and sustainability goals, and who seek to drive industrial and/or societal change. This thesis thereby sets out to explore how the two processes of market shaping and hybrid new venture development are interrelated. To gain a holistic understanding, I draw from research on market shaping, hybrid entrepreneurship, and new venture development. The research process is abductive, iterating between theory and empirical data. Empirical knowledge is acquired through qualitative inquiry from a follow-up case study in the market for Guarantees of Origin (GO) for renewable electricity. As the main theoretical contribution, this study presents a process model of the intertwinement of hybrid new venture development and market shaping. The model shows this intertwinement as driven by four continuous, interrelated, and reciprocal subprocesses: visioning, legitimizing, engaging, and equipping. The findings illustrate that market shaping extends to the early stages of hybrid new ventures, and that their initial market shaping actions are taken long before they become legal business entities. Furthermore, the study extends current knowledge on the content of market shaping (i.e., what it is exactly that market shapers strive to shape and how) and provides a more nuanced understanding of the market shaping activities taken by the focal actor. The study also produces important implications for entrepreneurs and managers, enabling them to make more informed decisions related to their market shaping and to better navigate complex institutional environments.

-- Markkinoiden muokkaamisella tarkoitetaan toimijoiden määrätietoista pyrkimystä muuttaa markkinoiden ominaisuuksia tai rakentaa uusia markkinoita. Nykytutkimus yritysten välisen markkinoinnin alalla on keskittynyt vakiintuneiden yritysten pyrkimyksiin parantaa kilpailullista asemaansa, jättäen huomiotta markkinoiden muokkauksen, jonka päämääränä on olemassa olevien markkinoiden uudistaminen kestävämpään suuntaan. Lisäksi ymmärrämme vain vähän siitä, kuinka uudet hybridiyritykset muokkaavat markkinoita, vaikka digitalisaatio luo ennennäkemättömiä mahdollisuuksia pienten yritysten muutostoimijuudelle. Hybrideillä tarkoitetaan uusia yrityksiä, jotka tavoittelevat sekä kaupallisia, että kestävään kehitykseen liittyviä päämääriä ja jotka myös pyrkivät ajamaan teollista ja/tai yhteiskunnallista muutosta. Tämän tutkimuksen tarkoituksena onkin ymmärtää, kuinka markkinoiden muokkausprosessi ja hybridiyrityksen kehitysprosessi ovat sidoksissa toisiinsa. Kokonaisvaltaisen ymmärryksen saamiseksi työssä hyödynnettiin markkinoiden muokkaamista, hybridiorganisaatioita ja uusien yritysten kehittämistä koskevaa tutkimusta. Tutkimusprosessi oli abduktiivinen, liikkuen iteratiivisesti teorian ja empiirisen aineiston välillä. Empiirinen aineisto kerättiin osana laadullista tapaustutkimusta, jossa seurattiin reaaliajassa uusiutuvan sähkön alkuperätakuiden markkinoita muokkaamaan pyrkivää hybridiyritystä. Tärkeimpänä teoreettisena kontribuutiona tutkimus esittää prosessimallin uuden hybridiyrityksen kehittämisen ja markkinamuokkauksen yhteen nivoutumisesta, jota edistää neljä jatkuvaa ja vastavuoroista osaprosessia: visiointi, legitimointi, sitouttaminen ja varustaminen. Tulokset osoittavat, että markkinoiden muokkaaminen alkaa jo uuden yrityksen alkuvaiheista. Lisäksi tutkimus laajentaa nykyistä ymmärrystä markkinamuokkauksen sisällöstä (eli mitä toimijat tarkalleen ottaen pyrkivät muokkaamaan ja miten), sekä tarjoaa monimuotoisemman käsityksen päätoimijan toteuttamista markkinoiden muokkaustoimista sekä niihin vaikuttavista kontekstuaalisista tekijöistä. Tutkimuksen tulokset auttavat myös yrittäjiä ja yritysjohtajia tekemään tietoisempia päätöksiä pyrkiessään muokkaamaan markkinoita ja luovimaan monimutkaisissa institutionaalisissa ympäristöissä.